Deflection analysis of subsea manifold roof protection plate - Willy Wianta. (2013)
Subsea manifold may often be subjected to accidentally drop object from offshore equipment during commissioning. The design of roof protection plate is necessary to prevent damage to this offshore structure, ranging from extensive permanent plastic deformation to perforation of the members being impacted. The response of protection plate subjected to drop object impact was analysed by measuring the plate deflection on different plate thickness using numerical modelling and compared it to simple design formulas. The investigated cases involve 1 m to 4 m square steel plates subjected to drill collar impact with thickness ranging from 10 mm to 40 mm. As roof protection plate has cut-out holes for valves and actuators access, plate deflection with different orientation and number of cut-out holes was also investigated. The results obtained are thought to be of particular interest at the design stage as plate deflection can then be calculated easily with some simple design formulas. This will reduce computation time and resources at initial concept design stage necessary to anticipate the impact of drop object on roof protection plate.